Host associations and genetic diversity of bat flies (Diptera: Nycteribiidae and Streblidae) in bats from Thailand - Dimas Novianto; Siwaporn Tuangpermsub; Thongchai Ngamprasertwong; Morakot Kaewthamasorn (Parasites & Vectors)
Abstract Background Bat flies belong to the order Diptera and superfamily Hippoboscoidea. They can be divided into two families, Streblidae and Nycteribiidae, which collectively encompass 239 and 280 species worldwide, respectively. In Thailand, 43 species of Nycteribiidae and 16 species of Streblidae have been documented. Despite their diversity, the molecular characteristics and host-parasite interactions of these ectoparasites remain poorly understood. Methods During a bat survey conducted between 2019 and 2022, bat flies were collected across eight sites in three provinces of Thailand. Morphological identification was performed using identification keys and a bat fly checklist endemic to Thailand. DNA barcoding targeted to the mitochondrial Cox1 and nuclear 28S rRNA genes was utilized. Infestation patterns were analyzed in relation to host sex, sampling site, and physiological status. Species identification was confirmed via BLASTN searches, and species delimitation was conducted using the ASAP algorithm under three substitution models. Phylogenetic relationships were inferred using Maximum Likelihood methods, while genetic variation was assessed through TCS haplotype network analysis. Tripartite network analysis was employed to examine site-host-parasite associations. Results A total of 1,042 bats, representing 28 species, were captured during the study, of which 298 individuals (28.59%) were infested with bat flies. In total, 773 bat flies were collected, comprising 737 from the family Streblidae and 36 from Nycteribiidae. Morphological and molecular analyses identified three genera—Raymondia, Brachytarsina, and Nycteribia—along with seven hypothetical species. Phylogenetic reconstruction using mitochondrial (Cox1) and nuclear (28S rRNA) gene markers revealed distinct clades within each genus, underscoring substantial genetic diversity. Haplotype analyses identified 18 haplotypes in Raymondia, six in Brachytarsina, and two in Nycteribia, with evidence of site-specific host-parasite associations. Infestation rates varied by host species, sex, and location, with larger bat populations demonstrating higher infestation intensities. Raymondia sp. 1 is the most frequently encountred species an predominantly infested Hipposideros gentilis. Conclusions This study provides the first molecular characterization of bat fly diversity in Thailand, revealing their genetic complexity, taxonomy, host specificity, and ecological interactions. The findings establish a crucial foundation for further research concerning the biodiversity, host-parasite dynamics, and zoonotic risks associated with bat flies. Graphical Abstract